2019
DOI: 10.1186/s12978-019-0711-z
|View full text |Cite
|
Sign up to set email alerts
|

Developing integrated community-based HIV prevention, harm reduction, and sexual and reproductive health services for women who inject drugs

Abstract: Background Despite being a priority population for HIV prevention and harm reduction programs, the sexual and reproductive health (SRH) needs of women who inject drugs are being overlooked. Furthermore, models for providing integrated SRH, HIV, and harm reduction services for women who inject drugs are rare. This article reports the development of community-based outreach services that integrated family planning and other SRH interventions with HIV and harm reduction services for this population i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
23
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(25 citation statements)
references
References 34 publications
0
23
0
Order By: Relevance
“…11,12 NEPs are a longstanding harm reduction strategy that have been proven to minimize the reuse of needles and reduce overdose risk and the transmission of bloodborne pathogens. [13][14][15] Research also shows that people who use NEPs or a similar program, syringe services programs, are actually five times as likely to enter a drug treatment program than people who do not use these services. 16 Despite their effectiveness, NEPs remain a controversial topic and face many ongoing social and political obstacles from local communities, government, and law enforcement that are much more nuanced.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…11,12 NEPs are a longstanding harm reduction strategy that have been proven to minimize the reuse of needles and reduce overdose risk and the transmission of bloodborne pathogens. [13][14][15] Research also shows that people who use NEPs or a similar program, syringe services programs, are actually five times as likely to enter a drug treatment program than people who do not use these services. 16 Despite their effectiveness, NEPs remain a controversial topic and face many ongoing social and political obstacles from local communities, government, and law enforcement that are much more nuanced.…”
Section: Introductionmentioning
confidence: 99%
“…33 Previous studies that have examined religion's effect on substance use have found that religion can have a positive effect on prevention and recovery, as well as, be a major contributor to drug-related stigma. 35,36,39 Although previous studies have provided critical insights into the influence that rural faith-based institutions have on community health and the role of NEPs in the reduction of STI transmission and overdose risk, [13][14][15]35,36,39 there is a lack of research that investigates rural faith leaders' perceptions of harm reduction strategies, specifically NEPs. Exploring the perceptions of key community health leaders who can connect members to key social and health services and influence health programming is paramount.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…incb, 2016, 7 Women also face greater barriers to accessing harm reduction services and treatment in prison (Sander, Shirley-Beavan and Stone, 2019) and in the community. This is not exclusive to Latin America but can be defined as a global problem, with different countries providing different levels and quality of access (Ayon et al, 2019;Médecins du Monde, 2019;Uusküla et al, 2018); furthermore, women who use drugs and are victims of violence are usually denied access to shelters for women victims of violence based on their drug use, either by law or by institutionalised practice, thus leaving them and their children in a situation of further vulnerability due to the actions of state and private institutions (Benoit and Jauffret-Roustide, 2016;hri, 2013).…”
Section: 2mentioning
confidence: 99%
“…incb, 2016, 7 Women also face greater barriers to accessing harm reduction services and treatment in prison (Sander, Shirley-Beavan and Stone, 2019) and in the community. This is not exclusive to Latin America but can be defined as a global problem, with different countries providing different levels and quality of access (Ayon et al, 2019;Médecins du Monde, 2019;Uusküla et al, 2018); furthermore, women who use drugs and are victims of violence are usually denied access to shelters for women victims of violence based on their drug use, either by law or by institutionalised practice, thus leaving them and their children in a situation of further vulnerability due to the actions of state and private institutions (Benoit and Jauffret-Roustide, 2016;hri, 2013).…”
Section: 2mentioning
confidence: 99%